2022
DOI: 10.5811/westjem.2022.4.55582
|View full text |Cite
|
Sign up to set email alerts
|

Intimate Partner Violence, Sexual Assault, and Child Abuse Resource Utilization During COVID-19

Abstract: Introduction: Key measures in preventing spread of the virus that causes coronavirus disease 2019 (COVID-19) are social distancing and stay-at-home mandates. These measures along with other stressors have the potential to increase incidences of intimate partner violence (IPV), sexual assault, and child maltreatment. Methods: We performed a retrospective review of county police dispatches, emergency department (ED) visits, Sexual Assault Nurse Examiner (SANE) consults, Domestic Violence Healthcare Project (DVH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 19 publications
1
7
0
Order By: Relevance
“…The study also found that there was a noticeable disruption in several service indicators related to child wellbeing, service delivery, and access to services [ 17 ]. A reduction in hospital deliveries, c-sections, family planning consultations, and child vaccinations was also confirmed by a mixed-methods comparative study conducted in Mozambique [ 18 ].…”
Section: Introductionmentioning
confidence: 79%
“…The study also found that there was a noticeable disruption in several service indicators related to child wellbeing, service delivery, and access to services [ 17 ]. A reduction in hospital deliveries, c-sections, family planning consultations, and child vaccinations was also confirmed by a mixed-methods comparative study conducted in Mozambique [ 18 ].…”
Section: Introductionmentioning
confidence: 79%
“…Overall CPS reports were significantly lower during this period due to lack of reports made by schools and families remaining at home (Baron et al, 2020). However, reports of IPV were increased (Pallansch et al, 2022) and police calls for service for IPV when there are children in the home are reported to CPS. Since cases were matched for both F4C and the control group for the same time period, we do not expect any differential impact on one group versus the other.…”
Section: Discussionmentioning
confidence: 99%
“…Data on IPA comes from a variety of sources, captures different content, varies in quality, and often does not account for confounding factors. Key sources include the police (e.g., calls for service, arrests; Lausi et al, 2021;Pallansch et al, 2022;Trafford, 2022); IPV services (e.g., calls to hotlines, service utilization; Brink et al, 2021;Pallansch et al, 2022;Perez-Vincent et al, 2020;Romito et al, 2022;Soeiro et al, 2023); and health services (medical reports, health records; Gosangi et al, 2021;Hoffman et al, 2023;Lausi et al, 2021). Reporting may have increased as an extension of help-seeking and significant life changes, as observed in other natural disasters, and because people recognized acts as abusive that previously went unacknowledged (e.g., minor or infrequent IPA, or IPA by a new partner; Kaukinen, 2020;Trafford, 2022).…”
Section: (How) Did Ipa Change During the Pandemic Period?mentioning
confidence: 99%
“…Monitoring also changed outside the home. Partners were, by definition, isolated from external parties who might monitor IPA, both formally-for example, health or social services (Lausi et al, 2021;Pallansch et al, 2022)-and informally-for example, friends and family (Andrade et al, 2022;Canzi et al, 2021;Vergauwen et al, 2022). However, the more continuous presence of neighbors counterbalanced some of the reduction in external monitoring, as evidenced by an increase in third-party calls to IPA services (Coomans et al, 2023;Eichelsheim et al, 2023;Ivandic et al, 2020;Perez-Vincent et al, 2020), potentially amplified by measures encouraging monitoring and reporting.…”
Section: Opportunity Theoriesmentioning
confidence: 99%
See 1 more Smart Citation